The ambitious anesthetist aiming for zero nausea/vomiting: can a €55 gram of prevention obviate a €5,000 kilogram of cure? A cost-minimization and cost-benefit perspective - Williams, Brian A.; La Colla, Luca; Smith, Kenneth J. (Frontiers in Anesthesiology, 2025)
We present cost-minimization and cost-benefit perspectives related to postoperative nausea/vomiting (PONV) strategies. Ongoing consensus guideline use (2003-2020) is characterized as high-frequency “€5,000 Kilogram of Cure” (related to high-cost hospital rescue/workup after “€3 Milligram of Prevention,” averaging €2,500/patient); this was compared to an innovative “5+ 3, €55 Gram of Prevention” technique, entailing 5-drug prophylaxis (palonosetron, perphenazine, aprepitant, diphenhydramine, dexamethasone), and 3-drug boosters (with these italicized agents). The €55 Gram of Prevention front-loaded cost increase (followed by a €500 “Gram of Cure” lower average cost, based on 90+% prophylactic efficacy) assumes lower associated PONV incidence/costs, during which downstream, in-hospital consensus-guided €5,000/patient Kilogram of Cure costs are strategically avoided via prevention beyond consensus-guided €3 Milligram of Prevention. Cost-minimization and cost-benefit tables are provided, incorporating existing cost outcomes from United States data sets. Comparative cost outcomes are adapted to a sovereign nation's internet postings of health economic “cost quadrants,” motivated by cost savings and outcome improvement via early prevention, as opposed to low-cost prevention and high-cost outcome variability. The 5 + 3 technique substitutes palonosetron (twice preventatively, 40 h apart) for ondansetron (q4 h, and risking rebound PONV), rendering the 5 + 3 technique as (i) cost-minimizing, and (ii) showing an incremental cost-benefit ratio that would favor preventative policy acceptance. The 5 + 3 technique representing €55 Gram of Prevention appears to obviate €5,000 Kilogram of Cure in 50% of patients represented by 2003–2020 consensus guidelines, with the consensus-guided approach being harmed by the enticements of low-cost and short-duration prophylactic and rescue ondansetron, carrying costly rebound (vs. breakthrough) PONV risks that have been previously reported.